ANALISIS USAHATANI KAKAO RAKYAT DI BERBAGAI POLA TANAM TUMPANG SARI - Hariyati, Yuli (Jurnal Agribisnis Indonesia, 2013)
The contribution of cocoa plantations to the income of farmers is an important issue for farm-scale development. Cocoa plant is an annual plant that is capable of producing a year only once. In order to earn income every month, the farmers implement intercropping pattern in their cocoa farming folk. Application of intercropping patterns on their farm has a linkage with the components of the costs incurred to cultivate these plants. This research was carried out to determine: (1) the application of intercropping patterns and the reasons for choosing one type of intercropping pattern on cocoa farming folk; (2) the differences of cost efficiency in each intercropping patterns on cocoa farming folk; (3) the differences ofÂ profitability in each intercropping patterns on cocoa farming folk; (4) the differences of labor productivity in each intercropping patterns on cocoa farming folk. This research location was decided by purposive method in Subak Abian Amertha Nadi, Yeh Embang Kauh Village, Mendoyo Distric. The research method which are used in this research are descriptive, comparative and analytical. Data analysis method which are used in this research are R/C ratio, revenue analysis, and labor productivity. The research results showed that : (1) cloves provide the greatest contribution to revenue in the fourth intercropping patterns and the farmers reasons for choosing intercropping patterns, among others : hereditary system, large gains, increasing yields, profits every time, and risks of failure; (2) cost efficiency among the four intercropping patterns were not significantly different, (3) gains among the four intercropping patterns were not significantly different; (4) labor productivity among the four intercropping patterns also were not significantly different.